Human Umbilical Cord Blood Cells Directly Suppress Ischemic Oligodendrocyte Cell Death - Hall, A.A. (2009)
Previous reports have shown that human umbilical cord blood cells (HUCBCs) administered intravenously 48 hrs following middle cerebral artery occlusion reduces infarct area and behavioral deficits of rodents. This cellular therapy is potently neuroprotective and anti-inflammatory. This study investigates the effect of HUCBC treatment on white matter injury and oligodendrocyte survival in a rat model of ischemia. Intravenous infusion of 10(6) HUCBCs 48 hrs post-stroke reduced the amount of white matter damage in vivo as seen by quantification of myelin basic protein staining in tissue sections. To determine whether HUCBC treatment was protective via direct effects on oligodendrocytes, cultured oligodendrocytes were studied in an in vitro model of oxygen glucose deprivation. Active caspase 3 immunohistochemistry and the LDH assay for cytotoxicity were used to determine that HUCBCs provide protection to oligodendrocytes in vitro. Based on these results, it is likely that HUCBC administration directly protects oligodendrocytes and white matter. This effect is likely to contribute to the increased behavioral recovery observed with HUCBC therapy.